Childhood Obesity in America: The Leadership Role of Schools in Prevention - Daphnee A. Guillaume (University of North Florida, 2011)
Childhood obesity is a major public health concern; children are being diagnosed with adult type diseases and health conditions, such as type 2 diabetes, hypertension, cardiovascular disease, etc. Still, over the past decade there have been many attempts by schools, and even the federal government to address the situation, yet there hasn't been an effective model that has been able to do so. The schools in this country are not consistent when it comes to addressing the issue of childhood obesity. Out of the 50 states in this country, only 19 have nutritional standards for school meals, though all 50 states have some form of physical education requirements, some students are still not getting the necessary (150 minutes per week) physical activities in school. Through John Kotter's 'Eight-stage process for creating major change', we cannot only continue to include school officials and teachers as part of the process, but we would be able to include, public health officials, parents, community leaders, and the students to come together to fix this matter.